Competing for capital : - Marcus, Bruce W. (John Wiley & Sons, 2005)
isclosure has always been the touchstone of securities laws, but now more disclosure is required on a real-time basis with heightened accountability. Competing for Capital is a must-read for those in the securities industry, providing insights into securities markets, the information age and technology, and their impact on the job of investor relations professionals. Investors come in all shapes and sizes from around the globe, and investor relations personnel have their work cut out for them to provide clear, comprehensible, and comprehensive information, accessible to the novice and sophisticate alike